Polícia versus democracia : a produção acadêmica sobre violência policial no Brasil - Santos, Lucas da Silva (2021)
The present dissertation is inserted in the concentration area “Penal System and Violence” and research line “Violence, Crime and Public Security”, of the Postgraduate Program in Criminal Sciences of the Pontifical Catholic University of Rio Grande do Sul, under the guidance Professor Augusto Jobim do Amaral and under the coorientation of Doctor Felipe da Veiga Dias. The research has as it’s subject police violence, with the analysis of academic production on police violence in Brazil as it’s delimitation. The main objective of the research is to complexify the concept of "police violence", to this end, a survey of doctoral thesis was made, available in the Catalog of Thesis and Dissertations of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), which have police violence as a primary object of the research, which is justified in understanding what is meant by the expression “police violence”, in the thesis object of the meta-analysis carried out in this dissertation. It starts from the following research problems: which are the meaning and/or concept of “police violence” attributed by doctoral thesis? Are these meanings restrictive or extensive? The research is divided into three chapters, in the first chapter, the meta-analysis of academic production was carried out, using the prevalent inductive approach method, and with deductive constructions. Following, based on the deductive approach, and with research techniques of indirect documentation, with bibliographic emphasis, we sought to explore the emergence of the modern police in Brazil, its historical antecedents, advancing in decisive periods – Imperial Age, Vargas’ dictatorship, civil-military dictatorship (1964-1985), redemocratization until the democratic period. Finally, in the last chapter, it focused on the articulations between securitizations and peacemaking policies, the consolidation of security democracy in Brazil, and based on Foucault's readings, the role of the police in the art of governing populations. It is concluded that the diffuse violence of the Brazilian police and its sovereign authority, historically presented as “necessary”, cannot be reduced to an expression or concept, the exercise of violent, authoritarian and violating practices against the population is more profound than one majority orientation of what was conventionally called “police violence”.